STUDENTS STRATEGIES IN COMPREHENDING READING SECTION ON TOEFL AT ENGLISH HOME COMMUNITY AT THE FORT ORANJE TERNATE - Harni A. Musa; Saiful Latif; Naniek Jusnita; Safrin Hamataher (Jurnal Bilingual, 2022)
The purpose of this research to know the students strategies in comprehending reading section on TOEFL at the English Home Community. The researcher applied qualitative research to explore students strategies in comprehending reading section on TOEFL at the English Home Community. The subjects were ten students at the English Home Community. The instrument were questionnaire and interview. It was found that reading comprehension on TOEFL section used by the English Home Communitys students are: students of English Home Community read the question first, read the direction, find out the meaning of unfamiliar words by using context, do skimming and scanning reading strategy, guessing the meaning by using background knowledge, reading the key words and reading the text first.